A contextual analysis of the university research agenda of select teacher education institutions in the Philippines: policy implications and future directions / Steven L. Baylan - Baylan, Steven L. (Universiti Teknologi MARA, 2023)
With the promising developments in regional cross-border in South-East Asia, Higher Education Institutions chart a well-articulated and relevant research agenda because of the pivotal role in regional eminence and competitiveness. Using contextual analysis to unfold what characterises the University Research Agenda (URA) of the leading (n=8) Teacher Education Institutions (TEIs), the findings revealed a culturalist research agenda characterised by a contextual trend toward sustaining institutional development and social transformation, expanding institutional linkages and network, and fostering university identity crafted in a multi-sectoral approach. In addition, an overwhelming number of external drivers on the research agenda compared to international drivers denote a domestic in-scope research agenda. The study contends that for TEIs to deter a regional roadmap creep, an isomorphism in the research agenda that espouses university identity infused with regionalisation ideologies to contribute to mapping the regional landscape of HE. The paper also draws implications on policy reforms, research agenda reframing, and suggestions for TEIs’ future direction.